A mitigação dos prejuízos sob a perspectiva do Direito brasileiro - Calfat, Mariana Marques (2016)
The paper is a study of the doctrine of avoidable damages under the light of the Brazilian law, which, unlike other systems, does not expressly predict the existence of the burden of mitigation. It tries to insert the concept of the duty to mitigate losses in this specific context, pointing out the main features of its institution, foundations, structure and growth prospects. Synthetically, this dissertation is divided into six chapters. The first chapter, theoretical framework, consists of opening remarks on the standards surrounding mitigation. The second chapter highlights international initiatives. The third and fourth chapters deal with the implementation of duty to mitigate losses in the Brazilian civil law. The fifth chapter develops the question of assessing the reasonableness of mitigation measures. The sixth chapter moves away from the individual-patrimonial approach and proposes the inclusion of the burden of mitigation as a guideline for governing the use of social wealth, going to the economic repercussions arising from the institution of the concept. Throughout this study, it is sought to demonstrate that the law imposes a specific conduct in order to mitigate losses resulting from default, given that the institutionalization of the concept would bring greater security to the parties involved, including judges. Finally, using the method of economic analysis of the law, it was found that the rule of mitigation could be used as a guideline governing the use of social wealth, fostering cooperation that should exist between individuals in order to avoid waste of relevant economic and social resources